Savouring the Veiled Narratives of Banquet Menus - Adriana SOHODOLEANU (Cultural Intertexts)
The study explores the semiotic significance of late 19th to early 20th-century Romanian banquet menus, transcending culinary functions to convey broader societal messages. By examining thirty menus from Romania and Austro-Hungarian Romanian-speaking Transylvania, predominantly sourced from newspapers, it reveals banquets as platforms for political and social expression. Written in Romanian or French, these menus serve as conduits for political opinions, declarations of friendship or enmity, and expressions of pride or despair. Intentionally published in newspapers, they reflect a society valuing freedom of speech and exhibit a discernible discursive character, treating food as intellectual nourishment. The coverage of banquets in newspapers offers glimpses into contemporaneous events and personalities, serving as historical documents shedding light on overlooked events and individuals. Through the examination of these menus’ meanings, researchers gain insights into forgotten personalities and societal dynamics, illustrating the enduring cultural significance of food beyond mere sustenance.